Relative age effects as evidence of selection bias in Major League Baseball draftees (2013-2018) - Herring, C. H.; Beyer, K. S.; Fukuda, D. H. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to examine if relative age effects (RAEs) or the unequal birth-date distribution among a cohort group of individuals exist in Major League Baseball (MLB) draftees. This study comprised 7,078 men drafted in the MLB first-year player draft from 2013 to 2018. Data collected for each draftee included birth date, year drafted, academic-level classification, position, round drafted, batting side, and throwing arm. Draftee's birth dates were categorized into quarters based on the calendar year for baseball in the United States (Q1: August-October; Q2: November-January; Q3: February-April; Q4: May-July). Player birth-date distributions were compared with average expected birth-date distributions and evaluated with the Chi2 goodness of fit statistic. Significant Chi2 tests were followed up by calculating the standardized residual for each quarter. Differences from the expected frequencies were found for the overall group (p < 0.001) with standardized residuals for baseball athletes born in Q1 (z = +4.45) and Q3 (z = -4.15) exceeding ±2.0. Similar patterns were noted for high schoolers (Q1: z = +3.30; Q3: z = -3.28), pitchers (Q1: z = +2.78; Q3: z = -3.12), early middle rounders (Q1: z = +3.08; Q3: z = -2.67), late rounders (Q1: z = +2.70; Q3: z = -2.61), right-side hitters (Q1: z = +3.23; Q3: z = -2.26), left-handed pitchers (Q1: z = + 2.12; Q3: z = -2.59), and right-handed positional players (Q1: z = +3.12; Q3: z = -2.12). Consistent with the majority of previous research, RAEs are apparent in MLB draftees, with specific patterns of unequal distribution among subsets of athletes.